Semantic Web Application and Framework Development in South African Higher Education Institutions - Nwanua Ohei, Kenneth (International Journal of Criminology and Sociology, 2022)
The evolution of the Semantic Web (SW) and its application marked a turning point in how students could benefit from a range of educational web tools and applications enabled by the SW, also referred to as Web 3.0 technology for academic purposes to meet their demands. This shift afforded students the opportunity to obtain meaningful information, collaboration and data filtering to suit their needs. It also offers freedom in how and where they choose to learn. SW tools and applications are progressively being used at several universities worldwide. However, educators’ ability to integrate the use of these tools and applications in teaching and learning appears to be a major problem in almost every development plan of education and educational reform efforts. Moreover, very few educators integrate web tools to their full potential in teaching. This paper probed the integration and use of SW tools and applications in higher education institutions (HEIs), and developed a framework for its adoption in academic processes. The objectives aimed to establish the credible features and benefits of SW tools and applications in HEIs, and how the integration supports students’ academic goals. It is anticipated to improve learning interaction and collaboration, and build a social presence and cohesion among students. The paper employed a systematic literature review, and information and communication technology theory of adoption. The developed framework ultimately suggests that SW tools and applications are beneficial and useful in positively impacting the pedagogical setting. Findings revealed that certain challenges with human factors (technophobia, beliefs), infrastructure, security concerns, ethical and legal issues were identified as a hindrance to be considered during integration. Despite the challenges, these tools and applications provide variety and a new wave of teaching and learning in South African HEIs, which is crucial for meeting the demand of the Fourth Industrial Revolution (4IR) era.